Question
upstudy study bank question image url

For \( f(x)=x^{2}+5 \) and \( g(x)=\sqrt{x-1} \), find the following composite functions and state the domain of each. \( \begin{array}{lll}\text { (a) } f \circ g & \text { (b) } g \circ f & \text { (c) } f \circ f \\ \text { (d) } g \circ g \\ \text { (a) }(f \circ g)(x)=x+4 \\ \text { (Simplify your answer.) } \\ \text { The domain of } f \circ g \text { is } x \geq 1 .\end{array} \) (Type your answer in interval notation. Use integers or fractions for any numbers in the expression. Simplify your answer.)

Ask by Reeves Turnbull. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) \( (f \circ g)(x) = x + 4 \) with domain \( [1, \infty) \) (b) \( (g \circ f)(x) = \sqrt{x^2 + 4} \) with domain \( (-\infty, \infty) \) (c) \( (f \circ f)(x) = (x^2 + 5)^2 + 5 \) with domain \( (-\infty, \infty) \) (d) \( (g \circ g)(x) = \sqrt{\sqrt{x-1} - 1} \) with domain \( [2, \infty) \)

Solution

To find the composite functions and their domains, we will follow these steps for each composite function: 1. **Calculate the composite function.** 2. **Determine the domain of the composite function.** Let's start with each part: ### (a) \( f \circ g \) The composite function \( (f \circ g)(x) \) is defined as \( f(g(x)) \). 1. **Calculate \( f(g(x)) \)**: \[ g(x) = \sqrt{x-1} \] Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(\sqrt{x-1}) = (\sqrt{x-1})^2 + 5 = x - 1 + 5 = x + 4 \] 2. **Domain of \( f \circ g \)**: The domain of \( g(x) \) is \( x \geq 1 \) (since the square root function is defined for \( x-1 \geq 0 \)). Therefore, the domain of \( f \circ g \) is: \[ \text{Domain of } f \circ g: [1, \infty) \] ### (b) \( g \circ f \) The composite function \( (g \circ f)(x) \) is defined as \( g(f(x)) \). 1. **Calculate \( g(f(x)) \)**: \[ f(x) = x^2 + 5 \] Now substitute \( f(x) \) into \( g(x) \): \[ g(f(x)) = g(x^2 + 5) = \sqrt{(x^2 + 5) - 1} = \sqrt{x^2 + 4} \] 2. **Domain of \( g \circ f \)**: The function \( g(x) \) requires \( x - 1 \geq 0 \), which translates to \( x^2 + 5 - 1 \geq 0 \). Since \( x^2 + 4 \) is always non-negative for all real \( x \), the domain of \( g \circ f \) is: \[ \text{Domain of } g \circ f: (-\infty, \infty) \] ### (c) \( f \circ f \) The composite function \( (f \circ f)(x) \) is defined as \( f(f(x)) \). 1. **Calculate \( f(f(x)) \)**: \[ f(f(x)) = f(x^2 + 5) = (x^2 + 5)^2 + 5 \] 2. **Domain of \( f \circ f \)**: Since \( f(x) \) is a polynomial, it is defined for all real numbers. Therefore, the domain of \( f \circ f \) is: \[ \text{Domain of } f \circ f: (-\infty, \infty) \] ### (d) \( g \circ g \) The composite function \( (g \circ g)(x) \) is defined as \( g(g(x)) \). 1. **Calculate \( g(g(x)) \)**: \[ g(g(x)) = g(\sqrt{x-1}) = \sqrt{\sqrt{x-1} - 1} \] 2. **Domain of \( g \circ g \)**: For \( g(x) \) to be defined, we need \( x \geq 1 \). Now, we need to ensure that \( \sqrt{x-1} - 1 \geq 0 \): \[ \sqrt{x-1} \geq 1 \implies x - 1 \geq 1 \implies x \geq 2 \] Therefore, the domain of \( g \circ g \) is: \[ \text{Domain of } g \circ g: [2, \infty) \] ### Summary of Results - (a) \( (f \circ g)(x) = x + 4 \) with domain \( [1, \infty) \) - (b) \( (g \circ f)(x) = \sqrt{x^2 + 4} \) with domain \( (-\infty, \infty) \) - (c) \( (f \circ f)(x) = (x^2 + 5)^2 + 5 \) with domain \( (-\infty, \infty) \) - (d) \( (g \circ g)(x) = \sqrt{\sqrt{x-1} - 1} \) with domain \( [2, \infty) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the composite functions, we perform the following calculations: (a) \( f \circ g(x) = f(g(x)) = f(\sqrt{x-1}) = (\sqrt{x-1})^2 + 5 = x - 1 + 5 = x + 4 \). The domain of \( f \circ g \) is \( x \geq 1 \) because \( g(x) \) must be defined, which requires \( x - 1 \geq 0 \). (b) \( g \circ f(x) = g(f(x)) = g(x^2 + 5) = \sqrt{(x^2 + 5) - 1} = \sqrt{x^2 + 4} \). The domain of \( g \circ f \) is all real numbers \( \mathbb{R} \) since \( x^2 + 4 \) is always non-negative. (c) \( f \circ f(x) = f(f(x)) = f(x^2 + 5) = (x^2 + 5)^2 + 5 = x^4 + 10x^2 + 25 + 5 = x^4 + 10x^2 + 30 \). The domain of \( f \circ f \) is also all real numbers \( \mathbb{R} \). (d) \( g \circ g(x) = g(g(x)) = g(\sqrt{x-1}) = \sqrt{\sqrt{x-1} - 1} \). The domain of \( g \circ g \) is \( x \geq 2 \) because \( \sqrt{x-1} \) must be at least 1 for \( g \) to be defined. To summarize: - \( (f \circ g)(x) = x + 4 \) with domain \( [1, \infty) \) - \( (g \circ f)(x) = \sqrt{x^2 + 4} \) with domain \( (-\infty, \infty) \) - \( (f \circ f)(x) = x^4 + 10x^2 + 30 \) with domain \( (-\infty, \infty) \) - \( (g \circ g)(x) = \sqrt{\sqrt{x-1} - 1} \) with domain \( [2, \infty) \)

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy